Functional Exploration of Chaperonin (HSP60/10) Family Genes and their Abiotic Stress-induced Expression Patterns in Sorghum bicolor - Nagaraju, M.; Kumar, Anuj; Jalaja, N.; Rao, D. M.; Kishor, P.B. Kavi (Current Genomics, 2021)
Background: Sorghum, the C4 dry-land cereal, important for food, fodder, feed and fuel, is a model crop for abiotic stress tolerance with smaller genome size, genetic diversity, and bioenergy traits. The heat shock proteins/chaperonin 60s (HSP60/Cpn60s) assist the plastid proteins, and participate in the folding and aggregation of proteins. However, the functions of HSP60s in abiotic stress tolerance in Sorghum remain unclear. Methods: Genome-wide screening and in silico characterization of SbHSP60s were carried out along with tissue and stress-specific expression analysis. Results: A total of 36 HSP60 genes were identified in Sorghum bicolor. They were subdivided into 2 groups, the HSP60 and HSP10 co-chaperonins encoded by 30 and 6 genes, respectively. The genes are distributed on all the chromosomes, chromosome 1 being the hot spot with 9 genes. All the HSP60s were found hydrophilic and highly unstable. The HSP60 genes showed a large number of introns, the majority of them with more than 10. Among the 12 paralogs, only 1 was tandem and the remaining 11 segmental, indicating their role in the expansion of SbHSP60s. Majority of the SbHSP60 genes expressed uniformly in leaf while a moderate expression was observed in the root tissues, with the highest expression displayed by SbHSP60-1. From expression analysis, SbHSP60- 3 for drought, SbHSP60-9 for salt, SbHSP60-9 and 24 for heat and SbHSP60-3, 9 and SbHSP10- 2 have been found implicated for cold stress tolerance and appeared as the key regulatory genes. Conclusion: This work paves the way for the utilization of chaperonin family genes for achieving abiotic stress tolerance in plants.
Keywords: abiotic stress-responsive